Role of Facebook in Creating Social Awareness - Mohamed, SH Sheik (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Evolution of Facebook has suggested the richness of new media for effective communications to engage users. This paper present the results literature review that focus on usage of Facebook increasing social awareness among users, this study also showcases literature on how Facebook is effectively used for creating environmental awareness like climate change and environmental degradation etc. Some of the finding suggests that students and teachers rely on Facebook in order to conduct classes and to attend sessions. Another finding is that Facebook has become a medium to mobilize and organise people for cause and social awareness campaigns run by Non-governmental organisations and governmental organisations as a part of their social corporate responsibility. How to cite this article: Mohamed SHS. Role of Facebook in creating Social Awareness. J Adv Res Jour Mass Comm 2018; 5(4): 131-135.